2021
DOI: 10.1039/d0ra09706c
|View full text |Cite
|
Sign up to set email alerts
|

Influences of a standardized food matrix and gastrointestinal fluids on the physicochemical properties of titanium dioxide nanoparticles

Abstract: In this study, a standardized food model (SFM) and simulated gastrointestinal fluids have been used to study the fate of e-TiO2-NPs following a three-step digestion model in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…The lack of significant effect on cells in mice fed through food pellets could be due to the binding of food components on the NPs forming a protein/biomolecule corona, which could affect interaction with immune cells. Indeed, in vitro and/or in vivo studies demonstrated that food components influence the absorption and toxicity of inorganic NPs, such as zinc oxide (ZnO), 59 , 60 silver (Ag), 61 , 62 titanium dioxide ( ), 63 , 64 and . 65 , 66 In addition, amorphous silica NPs enhanced exogenous antigen entry and cross-presentation in vitro in murine DC, and this effect was suppressed after the modification of the NPs with either surface amine groups or carboxyl groups.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant effect on cells in mice fed through food pellets could be due to the binding of food components on the NPs forming a protein/biomolecule corona, which could affect interaction with immune cells. Indeed, in vitro and/or in vivo studies demonstrated that food components influence the absorption and toxicity of inorganic NPs, such as zinc oxide (ZnO), 59 , 60 silver (Ag), 61 , 62 titanium dioxide ( ), 63 , 64 and . 65 , 66 In addition, amorphous silica NPs enhanced exogenous antigen entry and cross-presentation in vitro in murine DC, and this effect was suppressed after the modification of the NPs with either surface amine groups or carboxyl groups.…”
Section: Discussionmentioning
confidence: 99%
“…There was a slight reduction in particle size as the coated nanoparticles passed through the gastrointestinal tract, suggesting that there was some disruption of the nanoparticle aggregates. 48,49 This effect may have been due to the changes in solution conditions, molecular interactions, and enzyme activity discussed earlier. For instance, some of the whey proteins may have been hydrolyzed by digestive enzymes in the stomach and the small intestine.…”
Section: Particle Size and ζ-Potential Changes Duringmentioning
confidence: 98%
“…The transformations of food-relevant NPs in the simulated gastrointestinal fluids have been investigated in several studies. 24,25,46,47 It has been shown that in simulated oral digestion step NP properties are relatively less modified than in the gastric or intestinal phases, 46,47 while protein corona formation on NPs in saliva has been shown to be NP type-dependent and potentially affect the digestive and antimicrobial properties of saliva. 48 However, previous studies have not considered the combined effects of the salivary environment and bacterial secreted compounds on NP transformation.…”
Section: Transformation Of Nps and Food-grade Tio 2 In Spent Artifici...mentioning
confidence: 99%